A Vision of equality looking into the political advertisement ban - Panganiban, Robert M.
The study focuses on the Political Advertisement Ban and its effectiveness in promoting equality among politicians especially during the 1998 elections. The Political Advertisement Ban regulates the media in such a way that all the candidates for government positions are given equal exposure. The first part of the study focuses on the politicians. It presents different methods or techniques that were utilized to gain additional media exposure for certain candidates for public offices. The second part of the study focuses on the religious group leaders. It presents the intervention made by the religious leaders in politics through the newspaper medium. It also presents the conflict among the Catholic Church, the media (the Philippine Daily Inquirer in this case), and other religious groups. The third part of the study focuses on recent moves to repeal the Political Advertisement Ban. It presents arguments thrown against the Political Advertisement Ban. The results of this study suggest that the Political Advertisement Ban should be repealed.